Interdisciplinarietà e innovazione - Rossella Bonito Oliva (S&F_scienzaefilosofia.it, 2014)
Talking about Interdisciplinary means to define methodological ranges and spheres of research which in the progress of Knowledge seem to open wide in a more and more significant way. But on the back of the order of things it seems to arise the only Mind that, in different spheres, always goes toward the connection of phantasy, representation and reason.